Comparison Of Formulations And Antioxidant Activity Of Transparent Soap From Red And Black Plum (Prunus domestica L.) - Yessi Febriani; Mierza, Vriezka; Septimar, Elviza (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2021)
Transparent soap is a type of soap for the face and body to cleanse and protect the skin from free radicals. Plums are fruits that have very high antioxidant capabilities, because they have the content of flavonoids and tannins. This research aims to make transparent soap with the addition of red and black plum juice and compare the antioxidant activity capabilities of soap. This research captures the process of taking cider, phytochemical screening, and soap making. Analysis is pH test, moisture content, foam stability, free alkaline, and antioxidant activity test with DPPH method. The results of the antioxidant activity test are very strong with a value of IC50 < 50 ppm namely red plum juice (30.83 ppm), black plum juice (47.74 ppm), red plum soap (16.52 ppm), black plum soap (12.08 ppm). Soap has a pH of negative blanko (8.5), positive blanko (8.3), red plum (8.6), black plum (8.0). Water content of blanko soap is negative (1.88), blanko positive (2.69), red plum (1.76), black plum (1.83). Negative blanko soap foam stability (50), positive blanko (20), red plum (45), black plum (65), and alkaline free negative blanko soap (0.04), positive blanko (0.08), red plum (0.05), black plum (0.06). Transparent soap meets the quality requirements in accordance with SNI 3532:2016.